2019
DOI: 10.1186/s12936-019-2706-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of malaria prevention among pregnant women and non-pregnant mothers of children aged under 5 years in Ibadan, South West Nigeria

Abstract: BackgroundAdequate knowledge of malaria prevention and control can help in reducing the growing burden of malaria among vulnerable groups, particularly pregnant women and children aged under 5 years living in malaria endemic settings. Similar studies have been conducted but with less focus on these vulnerable groups. This study assessed knowledge of malaria prevention and control among the pregnant women and non-pregnant mothers of children aged under 5 years in Ibadan, Oyo State, South West Nigeria.MethodsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
29
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 19 publications
15
29
3
Order By: Relevance
“…The current study revealed that educational status was also important variable which was significantly associated with knowledge on malaria among women of reproductive age. The finding of this study is in line with the studies that were conducted in Ghana [30], Nigeria [11], Burkina Faso and [22]. An explanation to this association may be due to the fact that educated mothers may not have problems to read and comprehend information concerning malaria.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study revealed that educational status was also important variable which was significantly associated with knowledge on malaria among women of reproductive age. The finding of this study is in line with the studies that were conducted in Ghana [30], Nigeria [11], Burkina Faso and [22]. An explanation to this association may be due to the fact that educated mothers may not have problems to read and comprehend information concerning malaria.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that people with low levels of individual health knowledge are greater than 2 times more likely to experience poor health outcomes [8]. Unfortunately, there are inconsistent and conflicting reports regarding the levels of Malaria knowledge and associated factors [9][10] [11] [12]. Previous studies have reported that women who reside in urban areas, women with better family monthly income, women who attended formal education have better knowledge regarding causes, signs and symptoms and preventive measures of malaria [10].…”
mentioning
confidence: 99%
“…The current study showed that educational status was an important variable which was signi cantly associated with knowledge on malaria among women of reproductive age. The nding of this study are in line with the studies that were conducted in Nigeria [13], Burkina Faso [24] and Ghana [33]. An explanation of this association may be due to the fact that educated mothers may not have problems reading and comprehending information concerning malaria.…”
Section: Discussionsupporting
confidence: 89%
“…It has been reported that people with low levels of individual health knowledge are greater than two times more likely to experience poor health outcomes [10]. Unfortunately, there are inconsistent and con icting reports regarding the levels of malaria knowledge and associated factors worldwide [11][12][13][14]. Previous studies have reported that women who reside in urban areas, women with better family monthly income, women who attended formal education have better knowledge regarding causes, signs and symptoms and preventive measures of malaria [12].…”
Section: Introductionmentioning
confidence: 99%
“…The current study showed that educational status was also important variable which was signi cantly associated with knowledge on malaria among women of reproductive age. The nding of this study is in line with the studies that were conducted in Nigeria [13], Burkina Faso [24], and Ghana [33], An explanation to this association may be due to the fact that educated mothers may not have problems to read and comprehend information concerning malaria. Another reason might be that, highly educated women may reside in richest households and urban areas where distance to health facilities may not be a big problem [38].…”
Section: Discussionsupporting
confidence: 88%